Trailer-mounted RFID reader scans EID tags during cattle shipments - Barnhardt, B.B.; Bryant, A.M.; Epp, M.P.; Spire, M.F.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One of the challenges regarding implementation of a national animal identification system is the logistics of reading and reporting EID (electronic identification) tag numbers as cattle move through the production cycle. Many small producers would have difficulty justifying the investment required to install an RFID (radio frequency identification) reader system that would only be used seasonally to track relatively small numbers of cattle that are entering commerce. A proposed solution to this issue is to install an RFID reader on commercial cattle trailers so that cattle can have EID tags read as they are loaded and unloaded during transport from one premise to the next. With such an arrangement, the RFID equipment would be used often by a small number of highly trained people in the transport sector and the cost could be spread over a large number of cattle hauled over the life of the reader. The goal of this study was to evaluate the performance of a trailer-mounted RFID reader, in one location, using four prominent brands of commercially available EID tags.
Keywords: Beef; Cattle; EID (electronic identification); RFID (radio frequency identification)